The Influence of Principal's Supervision and Participation of Committee on the Primary School's Performance in Pulau Rimau, Indonesia - Karso Karso; Muhammad Kristiawan; Yessi Fitriani (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
This paper aimed at determining the principal’s supervision and school committee participation on the primary school’s performance in Pulau Rimau, Indonesia. The sample of this research is 40 elementary school teachers. Data were collected using questionnaire and documentation. Data were analyzed using the SPSS program. The results showed 1) there was positive influence of principal’s supervision on the primary school’s performance; 2) there was positive influence of school committee participation on the primary school’s performance; 3) there was positive influence of principal’s supervision and school committee participation together on the primary school’s performance in Pulau Rimau, Indonesia. This paper contributed to principal on improving supervision and committee on participation in order to have very good primary school’s performance. Where the school wishes to have good performance they should have good principal’s supervision and committee’s participation.